Capital, the State and the Emergence of Class Relations: The Case of a Rural Community in Southern Philippines - Makol-Abdul, Pute @ Rahimah (1992)
The incorporation of Third World countries into the world capitalist system brought about far-reaching repercussions on the social, political and economic structures of less-developed societies. A study of the changes associated with capitalist penetration is therefore necessary to understand the contemporary situation of these societies. The present study was an attempt in this direction to understand the trans formative impact of the phenomenon at the village level. Primarily, it aimed at examining the dominating influence of capitalist penetration in the form of plantation agriculture on the nature and dynamics of class formation in the study area. Specifically,it investigated the following:(i) class structure and class relationships of Maguindanaons during the pre-plantation period; (ii) the process of penetration of plantations in Mindanao - Sulu and in the village in particular; and (iii)the relations of production that emerged as a result of the entry of the plantation.